Does Uncertainty Affect Corporate Investment Decisions? Evidence from Turkish Firms - Tan, Omer Faruk; Cavlak, Hakan; Cebeci, Yasin; Güneş, Necati (Asian Academy of Management Journal of Accounting and Finance, 2022)
In this study, we analyse the impact of uncertainty on the corporate investment of 164 Turkish manufacturing firms. The time covers the period from 2005 to 2019. Our results reveal that there is a negative association between corporate investment and uncertainty. Under uncertainty, firms opt to decline their investment. Additionally, financially constrained (non-dividend payers) firms are negatively affected more than financially unconstrained firms. The use of alternative measurements of uncertainty and investment ensures the validity of our results. Policymakers should deal with the uncertainty and implement economic policies to decrease the country’s risk premium.